2015
DOI: 10.1080/10962247.2015.1038398
|View full text |Cite
|
Sign up to set email alerts
|

Assessing future scenarios for health care waste management using a multi-criteria decision analysis tool: A case study in the Turkish West Black Sea Region

Abstract: The aim of this paper is to identify the best possible health care waste management option in the West Black Sea Region by taking into account economic, social, environmental, and technical aspects in the concept of multi-criteria decision analysis. In the scope of this research, three different health care waste management scenarios that consist of different technology alternatives were developed and compared using a decision-making computer software, called Right Choice, by identifying various criteria, meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 16 publications
(14 reference statements)
0
14
0
Order By: Relevance
“…Secondly, the use of a standard method for the assessment of solid waste management in any region and the spread of these studies in different regions will give researchers the ability to compare their results. As it is known, the use of different terminology in the solid waste literature causes the results obtained for different regions not to be compared or misinterpreted (Ciplak 2015). For example, when the values expressed by "amount of solid waste" are compared for cities A and B, it may be concluded that city A produces more solid waste.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, the use of a standard method for the assessment of solid waste management in any region and the spread of these studies in different regions will give researchers the ability to compare their results. As it is known, the use of different terminology in the solid waste literature causes the results obtained for different regions not to be compared or misinterpreted (Ciplak 2015). For example, when the values expressed by "amount of solid waste" are compared for cities A and B, it may be concluded that city A produces more solid waste.…”
Section: Resultsmentioning
confidence: 99%
“…Ciplak [7] recognize the best one in the waste management system of Turkish healthcare industry by using MCDM technique. The findings of the study displaying that landfilling disposal with the recovery of energy is the best one in the system and they give special care to segregation of waste.…”
Section: B To Identify the Waste In Healthcare Industry By Using Mcdmmentioning
confidence: 99%
“…From the above study, alternatives like sequential batch reactor and aerated lagoon acts as a major role in this process. Ciplak [22] conducted the assessment of waste management in the western sea zone of Turkish country by using MCDM method. The outcomes depict that technology with decentralized autoclaves is the most preferable option for waste management and they give more importance to the disposal by landfilling.…”
Section: Waste Managementmentioning
confidence: 99%